2006
DOI: 10.1007/s10682-006-9002-6
|View full text |Cite
|
Sign up to set email alerts
|

Cost and benefits of attractive floral traits in the annual species Madia sativa (Asteraceae)

Abstract: The maintenance of flower size variation within populations might be explained by conflicting selection pressures on floral traits that may involve biological agents, such as mutualists and antagonists, and allocation costs associated with floral display. The annual species Madia sativa (Asteraceae) exhibits ample variation in the number of ray florets in natural populations. This field study aimed at evaluating the costs and benefits associated with floral traits in M. sativa. In particular, we addressed two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 39 publications
0
23
0
Order By: Relevance
“…The extended duration of receptivity seen in F. semicordata can be interpreted as a response to the possibility of pollinator shortages that these factors generate, thereby increasing the reproductive success of the plants and benefitting the fig-fig wasp mutualism in general. As in other flowering plants, floral longevity reflects a balance between benefits and costs (Celedón-Neghme et al 2007;Castro et al 2008). The maintenance costs of retaining syconia are unknown, but in F. semicordata the syconia become less attractive and less likely to be pollinated as they become older and so are less efficient.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The extended duration of receptivity seen in F. semicordata can be interpreted as a response to the possibility of pollinator shortages that these factors generate, thereby increasing the reproductive success of the plants and benefitting the fig-fig wasp mutualism in general. As in other flowering plants, floral longevity reflects a balance between benefits and costs (Celedón-Neghme et al 2007;Castro et al 2008). The maintenance costs of retaining syconia are unknown, but in F. semicordata the syconia become less attractive and less likely to be pollinated as they become older and so are less efficient.…”
Section: Discussionmentioning
confidence: 99%
“…In animal-pollinated plants, floral longevity (the length of time a flower has viable pollen and receptive stigmas) equates with the maximum period for which a flower can wait for a pollinator to arrive (Petanidou et al 2001;Celedón-Neghme et al 2007). Floral longevity can vary from hours to weeks in different plant species and reflects a balance between the benefits of increased pollinator visits and the costs of continued flower maintenance (Primack 1985;Ashman and Schoen 1994;Yasaka and Nishiwaki 1998;Abe 2001;Rathcke 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As we predicted, Xower size signiWcantly aVected RA; RA beneWts were previously shown to be high in smallXowered plants in this species (Elle and Carney 2003), but the larger number of populations studied here make a strong case for the generality of these results. Other studies have likewise indicated the importance of Xoral morphology for either the ability of plants to self autonomously or the potential RA beneWt of such selWng (Runions and Geber 2000;Celedon-Neghme et al 2007; but see Eckert and Schaefer 1998). Within Xower size categories, however, the RA beneWt did not vary with population size.…”
Section: B)mentioning
confidence: 93%
“…Extrinsic factors may also affect individual attractiveness for pollinators. For instance, the degree of isolation, i.e., the distance of a focal plant to neighbour plants, is often negatively associated with individual attractiveness (Dafni 1992;Celedón-Neghme et al 2007).…”
Section: Introductionmentioning
confidence: 99%